Tracing The CRISPR System in The Genomes of The Oscillatoria acuminata and Stanieria cyanosphaera Originated from Malalayang Waters - Laliboso, Jurwin A.; Rumengan, Inneke; Ginting, Elvy L.; Manembu, Indri S.; Mantiri, Desy M. H.; Kawung, Nickson J. (JURNAL PESISIR DAN LAUT TROPIS, 2026)
The CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats) system is a specific nucleotide sequence in genomes of certain bacteria and archaea that functions as an adaptive immune system against viral infections and foreign genetic elements. However, not all microorganisms possess CRISPR systems; therefore, bioinformatic approaches are required to trace the occurrence of CRISPR-Cas systems. The objective of this study was to detect CRISPR-Cas systems in genomes of Oscillatoria acuminata and Stanieria cyanosphaera. Both species were identified among 2679 operational taxonomic units (OTUs) of microorganisms associated with ascidian Lissoclinum patella originated from Malalayang waters, based on previously reported metagenomic analyses. These species were selected due to their relatively high abundance and the availability of complete genome sequence data in the NCBI database, which were downloaded as FASTA format and analyzed using CRISPRCasFinder software. The results showed that O. acuminata possesses a complete genome sequence of 7,689,443 bp, containing 80 CRISPR arrays, of which two arrays are associated with Cas systems, and a total of 338 spacers. In the other hand, S. cyanosphaera has a complete genome sequence of 5,041,209 bp, with eight CRISPR arrays, two of which are associated with Cas systems, and a total of 37 spacers. The detected CRISPR loci were visualized using CRISPRCasViewer in three display models: linear, circular, and scatter plot. Further studies are required to determine the specific types of CRISPR-Cas systems present in each microbial genome. Keywords: O. acuminata; S. cyanosphaera; bioinformatics; CRISPRCasFinder; CRISPRCasViewer   Abstrak Sistem CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats) merupakan susunan sekuens nukleotida spesifik dalam genom bakteri dan arkaea tertentu yang berfungsi sebagai  sistem imun adaptif mikroba terhadap serangan virus dan materi genetik asing. Namun, tidak semua mikroba memiliki sistem CRISPR, sehingga diperlukan pendekatan analisis bioinformatika untuk mendeteksi CRISPR. Tujuan penelitian ini adalah untuk menelusuri keberadaan sistem CRISPR-Cas pada genom Oscillatoria acuminata dan Stanieria cyanosphaera. Kedua 2 jenis mikroba ini ditemukan di antara 2679 operational taxonomic units (OTUs) mikroba yang berasosiasi dengan ascidia Lissoclinum patella dari perairan Malalayang, berdasarkan analisis metagenom yang telah dilaporkan sebelumnya.  Kedua spesies ini dipilih karena terdeteksi cukup melimpah, dan ketersediaan data urutan genom lengkap di NCBI. Data urutan genom diunduh dalam format FASTA dan dianalisis dengan perangkat lunak CRISPRCasFinder. Ternyata O. acuminata memiliki  sekuens genom  lengkap  7.689.443 bp dengan 80 unit  sistem CRISPR, dimana ada 2 unit dengan sistem Cas, serta 338 spacer. Sedangkan S. cyanosphaera memiliki sekuens genom lengkap sekitar 5.041.209 bp dengan 8 unit CRISPR, dan 2 unit dengan sistem Cas serta 37 spacer. Hasil deteksi CRISPR divisualisasikan menggunakan CRISPRCasViewer dalam tiga model tampilan, yaitu Linear, Circular, dan Scatter Plot. Selanjutnya, ke depan perlu penelusuran lebih lanjut untuk menentukan tipe CRISPR-Cas pada setiap genom mikroba tersebut. Kata Kunci: O. acuminata; S. cyanosphaera; bioinformatika; CRISPRCasFinder; CRISPRCasViewer